The Scoliosis Quandary: Are Radiation Exposures From Repeated X-Rays Harmful? - Paul A. Oakley DC, MSc; Niousha Navid Ehsani MD; Deed E. Harrison DC (SAGE Publishing, 2019)
X-rays have been the gold standard for diagnosis, evaluation, and management of spinal scoliosis for decades as other assessment methods are indirect, too expensive, or not practical in practice. The average scoliosis patient will receive 10 to 25 spinal X-rays over several years equating to a maximum estimated dose of 10 to 25 mGy. Some patients, those getting diagnosed at a younger age and receiving early and ongoing treatments, may receive up to 40 to 50 X-rays, approaching at most 50 mGy. There are concerns that repeated radiographs given to patients are carcinogenic. Some studies have used the linear no-threshold model to derive cancer-risk estimates; however, it is invalid for low-dose irradiation (ie, X-rays); these estimates are untrue. Other studies have calculated cancer-risk ratios from long-term health data of historic scoliosis cohorts. Since data indicate reduced cancer rates in a cohort receiving a total radiation dose between 50 and 300 mGy, it is unlikely that scoliosis patients would get cancer from repeated X-rays. Moreover, since the threshold for leukemia is about 1100 mGy, scoliosis patients will not likely develop cancers from spinal X-rays. Scoliosis patients likely have long-term health consequences, including cancers, from the actual disease entity itself and not from protracted X-ray radiation exposures that are essential and indeed safe.